Differences in transcriptomic and metabolomic analyses of metabolites of shoots on tea plants of different ages and relevant regulatory network - Li, Meng Yuan; Zhang, Yun Zhi; Zhang, Zi You; Zhang, Yan Hui; Ren, Qian Qian; Jin, Shan (Frontiers in Plant Science, 2023)
To investigate differences in fresh leaves of tea plants at different ages in gene expression, metabolism, and dried tea quality, and to provide references to a deep exploration on metabolite differential accumulation of fresh leaves of tea plants at different ages as well as the regulation mechanism, two groups of fresh leaves from tea plants at different ages (group JP: 20-, 200-, and 1,200-year tea plants; group YX: 50-, 100-, and 400-year tea plants) were chosen as materials, and their differences in gene expression, metabolites, and metabolic regulatory network were investigated by transcriptomics and metabolomics. A total of 12,706 differentially expressed genes (DEGs) were screened from the fresh tea leaves in the JP group, of which tea-20 vs. tea-200 had the largest number of DEGs, up to 9,041 (4,459 down-regulated genes, 4,582 up-regulated genes). A total of 644 common genes in the fresh leaves of three different ages of tea plants in the JP group were differentially expressed. A total of 8,971 DEGs were screened from the fresh leaf samples of tea plants in the YX group, of which the number of DEGs obtained in the tea-50 vs. tea-400 comparison combination was the largest with a total of 3,723 (1,722 up-regulated genes and 2,001 down-regulated genes). A total of 147 common genes were differentially expressed in the fresh leaves of three different tree ages in the YX group. The pathway enrichment analysis showed that most up-regulated DEGs and their related metabolic pathways were similar in the two groups, and that the metabolic pathways of common significant enrichment included flavonoid biosynthesis, phenylpropane biosynthesis, carbon metabolism, amino acid biosynthesis, and plant pathogen interaction. The metabolomics results showed that 72 and 117 different metabolites were screened from the JP and YX groups, respectively. Most of the different metabolites in the two groups were flavonoids, phenolic acids, amino acids, and their derivatives. Among them, the number of down-regulated flavonoids in older tea plants is generally higher than the number of up-regulated flavonoids. Moreover, according to the sensory evaluation results of dried tea of fresh leaves from tea plants of different ages, tea-1200 and tea-400 showed the highest sensory evaluation scores in their groups. With increase in plant age, the fragrance of the tea was more elegant, and it changed from a dense scent to a faint scent; the tea tasted sweet and its freshness increased, while the sense of astringency was weakened and the concentration declined. Therefore, the quality difference of tea of different tree ages is mainly related to secondary metabolic pathways such as the flavonoid biosynthesis pathway. With increase in tea age, a large number of gene expression in the flavonoid biosynthesis pathway is down-regulated, which reduces the content of bitter flavonoid substances in fresh leaves and makes tea soup more mellow.